Bamboo Fiber and Sugarcane Skin as a Bio-Briquette Fuel - Anna Brunerová; Hynek Roubík; Milan Brožek (Energies, 2018)
The present study deals with the issue of bio-briquette fuel produced from specific agriculture residues, namely bamboo fiber (BF) and sugarcane skin (SCS). Both materials originated from Thừa Thiên Huế province in central Vietnam and were subjected to analysis of their suitability for such a purpose. A densification process using a high-pressure briquetting press proved its practicability for producing bio-briquette fuel. Analysis of fuel parameters exhibited a satisfactory level of all measured quality indicators: ash content Ac (BF—1.16%, SCS—8.62%) and net calorific value NCV (BF—16.92 MJ∙kg−1, SCS—17.23 MJ∙kg−1). Equally, mechanical quality indicators also proved satisfactory; bio-briquette samples’ mechanical durability DU occurred at an extremely high level (BF—97.80%, SCS—97.70%), as did their bulk density ρ (BF—986.37 kg·m−3, SCS—1067.08 kg·m−3). Overall evaluation of all observed results and factors influencing the investigated issue proved that both waste biomass materials, bamboo fiber and sugarcane skin, represent suitable feedstock materials for bio-briquette fuel production, and produced bio-briquette samples can be used as high-quality fuels.